Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

If $A\approx B$ then $A^{C}\approx B^{C}$ where $B^{C}:=\{f|f:C\to B\}$

by ''$\approx$'' I mean equinumerous

Proof: By hypothesis $A\approx B\Rightarrow \exists T:A\to B$ which is bijective and $\exists T^{-1}B\to A$ which is also bijective.

let now $\sigma: B^{C}\to A^{C}$ be defined as $\sigma: f\to T^{-1}\circ f$, for some $f\in B^{C}$

how to show that this function is bijective?


$\sigma(f_{1})=\sigma(f_{2})\Rightarrow T^{-1}\circ f_{1}=T^{-1}\circ f_{2}\Rightarrow f_{1}=f_{2}$ right?


share|cite|improve this question
up vote 3 down vote accepted

Your proof of injectivity is right, because you have $$T^{-1}\circ f_1=T^{-1}\circ f_2$$ Now, pre-compose both sides by $T$, to obtain $$T\circ T^{-1}\circ f_1=T\circ T^{-1}\circ f_2$$ But $T\circ T^{-1}$ is the identity function on $A$, hence you can conclude.

For surjectivity, let $f:C\longrightarrow A$ be an element of $A^C$. You need a pre-image of $f$ via $\sigma$, i.e. a function $g:C\longrightarrow B$ such that $\sigma(g)=f$. Take $g:=T\circ f$. To verify that this is the right one you only need to apply the definition of $\sigma$, so: $$\sigma(g)=\sigma(T\circ f)=T^{-1}\circ T\circ f=f$$ as claimed.

share|cite|improve this answer

Yes, your proof of injectivity is fine.

For surjectivity, take $f:C\to A$. Then let $f' = T \circ f$. What is $\sigma(f')$?

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.